Geographical Distribution of Methane Hydrates and International Geopolitics of Energy: Resources in the Eastern Mediterranean. - Ioannis Mazis; Georgios Sgouros (Civitas Gentium, 2011)
Methane Hydrates are a new energy resource in the global energy market which has received extreme attention from a technological and geopolitical point of view. The reserve estimates exceed by far the overall estimates of all the other conventional energy reserves. With the existing technological know-how the exploitation of methane hydrates is expected to dominate the international energy market within the next 10-15 years. Methane hydrates have been mapped within the Hellenic Submarine Space and especially in the region of Kastellorizo, with whatever consequences it may have of geostrategic nature for the political decisions of Greece and its relations with the neighbouring countries and the delimitation of its EEZ.